Investigating the Impact of Intercultural Communicative Competence on EFL Master Students’ Intercultural Awareness and the Crucial Role of Social Media in Developing It - KAROBI, Imène (My University, 2023)
This research investigates the impact of intercultural communicative competence (ICC) on Master Two EFL students' intercultural awareness and the role of social media in developing ICC. The study employed a mixed-methods approach using a questionnaire and interviews with ICC teachers and students at the University of Mostaganem in Algeria. The results revealed that integrating ICC in language classes is essential for enhancing students' intercultural awareness and competence. Additionally, social media provides valuable opportunities for practicing ICC skills, such as interacting with people from different cultures and engaging with diverse perspectives. The study recommends integrating ICC since the first educational years for all language classes and that ICC teachers use social media and technology as teaching tools to promote intercultural learning and encourage students to engage in cross-cultural interactions. Also, it recommends organizing travels for students to enable them to see the real-world applications of language learning. This research contributes to understanding the significance of ICC and social media in language teaching and learning.
Case Study: Language and Communication Master Two at Mostaganem University
Keywords: Cross-cultural interactions; ICC; EFL students' intercultural awareness; social media